Investigation of an Insulator Flashunder in an 150 kV OTL of the Power System of Crete - Pylarinos, D.; Pellas, I. (Engineering, Technology & Applied Science Research, 2019)
Overhead Transmission Lines (OTLs) are used in Power Systems to carry High Voltage between substations, usually over long distances. Faults in OTLs are bound to happen and thus locating and coping with them is an important aspect of OTL’s operation and maintenance. These faults may be of temporary or permanent nature, with certain types of faults progressing over time from the first category to the second. Local weather may also have a direct effect on the occurrence of faults resulting to puzzling events. A special category, often complex in nature, is insulator faults. Insulators are used in OTLs to support phase conductors while not allowing current to flow through the tower’s body to the ground. Traditional ceramic insulators used materials such as porcelain and glass as insulation, but in the last decades composite insulators with two insulating parts (a glass core/rod and a rubber housing), have also known great use mainly due to their low weight and their capability to withstand pollution. However, they are subjected to certain faults unique to them, such as flashunders. Flashunder is a term commonly used lately to describe faults that are related to the rod/housing interface of composite insulators. Such faults are rather difficult to locate as the electrical discharge does not create an easily visible trace (as in the case of flashovers) or a permanent mechanical fault (as in the case of brittle fractures). Such a fault occurred for the first time in the Transmission System of Crete in 2019 and this paper follows and discusses the incident and the experience gained.